The Ethics of Interpretation in Maqāṣidi Exegesis: An Exploration of the Framework in Ibn Asyur's Muqaddimah - Aditya, Muhamad Anwar; Asfiya', Rofiqoh Nurul; Mubarak, M Yusril (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2025)
Maqāṣidi interpretation, as one approach to interpretation, provides a solution in the contemporary era, which is full of complex problems. However, some research and interpretation results sometimes produce conclusions that are contrary to the expected understanding, due to unfulfilled interpretation ethics. Therefore, this study aims to explore the ethics of an interpreter who interprets Qur'anic verses using the maqāṣidi approach according to the perspective of Ibn 'Asyur, a renowned interpreter known for his maqāṣidi interpretive style. The object of study and primary data in this research is the Muqaddimah Tafsīr al-Taḥrīr wa Tanwīr by Ibn 'Asyur. Significant findings from Ibn 'Asyur's thought affirm the existence of an epistemological revolution that balances textual literalism and the objectives of sharia, challenging the dominance of conservative interpretation without falling into unrestrained liberalism. If applied consistently, this approach can dismantle the stagnant authority of classical tafsir and open space for interpretations of the Qur'an that are more relevant to the challenges of the times. However, without a strong epistemological foundation, maqāṣidi tafsir risks becoming a tool for legitimizing overly flexible interpretations, thereby losing its authority as part of divine revelation.